2011
DOI: 10.1002/iub.463
|View full text |Cite
|
Sign up to set email alerts
|

The induction of anhydrobiosis in the sleeping chironomid: Current status of our knowledge

Abstract: An African chironomid, Polypedilum vanderplanki, is the only insect known to be capable of extreme desiccation tolerance, or anhydrobiosis. In the 1950s and 1960s, Hinton strenuously studied anhydrobiosis in this insect from a physiological standpoint; however, nobody has afterward investigated the phenomenon. In 2000, research on mechanisms underlying anhydrobiosis was resumed due to successful establishment of a rearing system for P. vanderplanki. This review is focused on the latest findings on the physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 74 publications
(82 reference statements)
1
101
0
2
Order By: Relevance
“…We found that D. variabilis exhibit a suite of biochemical and molecular responses that likely improves their survival during dehydration. Although we studied a single tick species, many of the responses, including up-regulation of stressresponse and proteolysis-related genes, are common across a diverse range of arthropods (Benoit and Denlinger, 2010;Cornette and Kikawada, 2011;King and MacRae, 2015;Teets et al, 2012), suggesting that our findings could be applicable to ticks in general; however, further study is needed to verify that all ticks respond similarly to dehydration. Despite these efforts to reduce stress, the ability of ticks to cope with desiccation is not particularly extraordinary, and their tolerance of ∼30% body water loss (Yoder et al, 2012) is similar to that of many terrestrial arthropods (Hadley, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that D. variabilis exhibit a suite of biochemical and molecular responses that likely improves their survival during dehydration. Although we studied a single tick species, many of the responses, including up-regulation of stressresponse and proteolysis-related genes, are common across a diverse range of arthropods (Benoit and Denlinger, 2010;Cornette and Kikawada, 2011;King and MacRae, 2015;Teets et al, 2012), suggesting that our findings could be applicable to ticks in general; however, further study is needed to verify that all ticks respond similarly to dehydration. Despite these efforts to reduce stress, the ability of ticks to cope with desiccation is not particularly extraordinary, and their tolerance of ∼30% body water loss (Yoder et al, 2012) is similar to that of many terrestrial arthropods (Hadley, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Arthropods have a variety of mechanisms for preventing and tolerating dehydration-associated damage, including changes in the expression of proteins such as heat shock proteins, antioxidant enzymes and aquaporins (Benoit and Denlinger, 2010;Cornette and Kikawada, 2011;King and MacRae, 2015). Additionally, accumulation of various molecules, including trehalose and glycerol, can have protective effects during dehydration by acting to prevent damage to cellular components (Michaud et al, 2008;Watanabe, 2006;Yoder et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…In our research group, we have been studying for a decade extreme desiccation tolerance, known as anhydrobiosis, in the African sleeping chironomid, Polypedilum vanderplanki (Hinton, 1951(Hinton, , 1960a(Hinton, , 1960bWatanabe, 2006). The expression of various chaperone proteins, antioxidants, and the ultimate vitrification of a trehalose matrix have been shown to be essential for successful anhydrobiosis (Kikawada et al, 2006;Sakurai et al, 2008;Cornette et al, 2010;Cornette and Kikawada, 2011). Recently, genomic DNA was shown to experience severe damage during anhydrobiosis and these damages were repaired slowly after rehydration .…”
Section: Introductionmentioning
confidence: 99%
“…Немногочисленные находки личинок при 320 -340 г/л не позволяют сделать однозначный вывод о том, что они могут нормально функционировать при такой солёности. Ряд видов хирономид может длительно находиться в состоянии ангидробиоза (Cornette, Kikawada, 2011). Возможно, некоторые стадии B. noctivagus могут переходить к ан-гидробиозу при высыхании или в условиях очень высокой солёности.…”
Section: результатыunclassified
“…Личинки некоторых видов Chironomidae способны находиться в неактивном со-стоянии ангидробиоза длительное время (Suemoto et al, 2004), вид Polypedilum vanderplanki Hinton, 1951 -до 17 лет (Cornette, Kikawada, 2011). Можно предполо-жить, что это характерно и для личинок B. noctivagus.…”
Section: результатыunclassified